Metabolic Activation of the Toxic Natural Products From Herbal and Dietary Supplements Leading to Toxicities - Wang, Yi-Kun; Li, Wen Qun; Xia, Shuang; Guo, Lin; Miao, Yan; Zhang, Bi-Kui (Frontiers in Pharmacology, 2021)
Currently, herbal and dietary supplements have been widely applied to prevent and treat various diseases. However, the potential toxicities and adverse reactions of herbal and dietary supplements have been increasingly reported, and have gradually attracted widespread attention from clinical pharmacists and physicians. Metabolic activation of specific natural products from herbal and dietary supplements is mediated by hepatic cytochrome P450 or intestinal bacteria, and generates chemical reactive/toxic metabolites that bind to cellular GSH or macromolecules (protein or DNA) and form reactive metabolites-GSH/protein/DNA adducts, which can result in toxicities. The present review focuses on the relation between metabolic activation and toxicities of natural products, and provides updated, comprehensive and critical comment on the toxic mechanisms of reactive metabolites. The key inductive role of metabolic activation in toxicity is highlighted, and frequently toxic functional groups of toxic natural products were summarized. The biotransformation of drug metabolizing enzymes or intestinal bacteria involved in metabolic activation were clarified, the reactive metabolites-protein adducts were selected as biomarkers for predicting toxicity. And finally, further perspectives between metabolic activation and toxicities of natural products from herbal and dietary supplements are discussed, to provide a reference for the reasonable and safe usage of herbal and dietary supplements.